Eksplorasi konsep penjumlahan, pengurangan dan pecahan campuran pada permainanan bang-jo-neng-teh-ru - Rosadi, Moch Roma Isa; Marhayati, Marhayati (Maliki Interdisciplinary Journal, 2024)
The purpose of this study is to describe the results of exploring the concepts of addition, subtraction, and mixed fractions in the traditional bang-jo-neng-teh-ru game. This research is a qualitative research with an ethnographic approach. Data collection through observation, literature study, and documentation. Data analysis by exploring the process of eliminating the bang-jo-neng-teh-ru game. The results of the exploration of the concepts of addition, subtraction, and mixed fractions occur in the elimination stage.